Incidence of Staphylococcus aureus on equipment from a gym of physical activities in Alfenas – MG (Research, Society and Development, 2021)
With an increasing demand for gyms, especially during summer, the risk of contamination rises despite preventive care. In many sports, exercising must require attention to hygiene, mainly due to great chances of contracting diseases. Staphylococcus aureus has widely spread caused by its ability to express various virulence factors, which can cause diseases ranging from simple to most severe infections as a pathogen. This paper investigates the incidence of Staphylococcus aureus in equipment from a gym of physical activities in Alfenas-MG and identifies the appropriate level about the importance of cleaning equipment. In this study, three collections were carried out per equipment in different places, at three times; totaled 54 samples. Staphylococcus aureus was identified by sowing in Mannitol Salt Agar, medium coloration and colonial morphology, catalase, and coagulase tests. Twenty-nine samples obtained growth from the sowings, being positive for gram staining, catalase, and coagulase. In samples with micro-organisms (53.70%) and correspondents (50%), gym-goers did not clean the equipment, and the others (50%) only used the individual towel. Therefore, the measures that can decrease the incidence of micro-organisms, particularly Staphylococcus aureus, are disinfecting with 70% alcohol and disposable paper before and after manipulating equipment in a gym.